Labor Reform in the Workers’ State: The Chinese Experience - Josephs, Hilary K. (Columbia Journal of Asian Law, 1988)
Labor law in many countries is an amalgamation of both private and public law. According to the private law model, which is closely associated with freedom of contract and laissez-faire capitalism, the state’s role is largely confined to providing a stable basis for the development of private economic relations. Under the public law model, which is relevant to an understanding of both modem capitalist and socialist countries, the state plays an active, interventionist role in shaping economic relations. In the labor area, it supplies the content of the employment relationship through statute and administrative regulation, e.g., regarding minimum wages and maximum hours of employment. In contemporary China, the public law aspect of labor law has been virtually exclusive. From the late 1950’s until just recently, the Chinese government has unilaterally determined the obligations and entitlements of the work force, particularly with respect to those individuals employed in state industrial enterprises. However, in recent years, through a series of regulations governing employment in state industrial enterprises, the Chinese government has acknowledged a need for private law in the field of labor relations. Within certain important boundaries, the parties in an employment relation- ship are now free to negotiate the terms of employment. In this context, the state’s primary role is to serve as a referee, intervening only if called upon to settle disputes. The growth of private law in the labor area is consistent with recent changes in China’s economic and legal systems which are designed to overcome the deficiencies of a bureaucratic planned economy. During the past decade, the central government, disappointed with the performance of large economic units, has encouraged the entrepreneurial efforts of individuals, families, and small business entities in an attempt to invigorate the economy.